POLYMERS IN CRIMINALISTICS: LATENT FINGERPRINT DETECTION AND ENHANCEMENT – AS OF IDEA TO PRACTICAL APPLICATION - Milasinovic, Nikola (NBP. Nauka, bezbednosti, policija, 2017)
The identification of latent fingerprints is crucial for the security agencies in order to identify persons suspected of having committed criminal acts. Latent prints, often remain as random impressions onto the surfaces of various objects. Huge progress has been made in the identification processes using rolled and plain impressions fingerprints, while detection and comparison of latent prints still remains a challenging task. In addition to the existing standardized methods, in this paper the possible utilization of natural and synthetic polymers and their conjugates with the same goal will be reviewed, by means of latent fingerprints detection and development.